2019
DOI: 10.3390/toxins11020119
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Common Pathogenic Mechanisms between Homo sapiens and Different Strains of Candida albicans for Drug Design: Systems Biology Approach via Two-Sided NGS Data Identification

Abstract: Candida albicans (C. albicans) is the most prevalent fungal species. Although it is a healthy microbiota, genetic and epigenetic alterations in host and pathogen, and microenvironment changes would lead to thrush, vaginal yeast infection, and even hematogenously disseminated infection. Despite the fact that cytotoxicity is well-characterized, few studies discuss the genome-wide genetic and epigenetic molecular mechanisms between host and C. albicans. The aim of this study is to identify drug targets and design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…is the most frequent cause of fungal disease in humans. By establishing genetic and epigenetic interspecies networks of different strains of Candida albicans and their hosts through two-sided NGS data identification, Yeh et al [ 38 ] extracted core host–pathogen cross-talk networks. In addition to screening and identifying specific fungal types, NGS can be used to assess AMR.…”
Section: Ngs and Antifungal Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…is the most frequent cause of fungal disease in humans. By establishing genetic and epigenetic interspecies networks of different strains of Candida albicans and their hosts through two-sided NGS data identification, Yeh et al [ 38 ] extracted core host–pathogen cross-talk networks. In addition to screening and identifying specific fungal types, NGS can be used to assess AMR.…”
Section: Ngs and Antifungal Resistancementioning
confidence: 99%
“…Furthermore, the functional channels and pathogenic and defense mechanisms of C. albicans were studied, as were potential drug targets and multiple-molecule drugs for treating C. albicans infections [ 38 ]. By combining NGS with Fourier transform infrared (FTIR) spectroscopy, 256 phenotypes and genotypes of pathogenic Candida strains were identified.…”
Section: Ngs and Antifungal Resistancementioning
confidence: 99%
“…Moreover, one study has proposed a mathematical model of the plant clock using biological hypotheses and parameters solved by optimization methods to gain insights into the clock components within core mechanisms [22]. Systems biology approaches have been used to identify essential biomarkers and propose potential drugs based on molecular mechanisms and pathogenic mechanisms in papillary thyroid cancer and two strains of Candida albicans infection [23,24]. Systems biology approaches with modeling techniques enable us to elucidate the pathways, which are critically involved in tumor formation and progression, consequences of altered cell behavior in tissue environment and effects of molecular therapeutics [25].…”
Section: Related Workmentioning
confidence: 99%
“…Different strains of Candida are known to cause infections. Recent epidemiological studies have shown that drug-resistant species of Candida, like C. glabrata, C. krusei, C. tropicalis, and C. parapsilosis, are gradually replaced C. albicans in diseases [12] . Due to the spread of fungal infections and the increase in the use of antifungal drugs such as azoles, a significant increase in the resistance of Candida species to antifungal compounds is expected [13] .…”
Section: Introductionmentioning
confidence: 99%